Pre-weaning mortality rates of Sudanese sheep under farm condition - Sulieman, A.H; El-Neew, W.M; El-Amin, E.R. (1983)
Causes of pre-weaning lamb losses under farm conditions were investigated among the Shugor and Dubasi ecotypes of the Sudan Desert sheep. On average, these losses accounted for 40.5% of the lamb crop, but for the separate ecotypes these figures were 44.3 and 36.7%, respectively, for the Shugor and Dubasi. Adult sheep mortality rate amounted to 25.4%, on average, during the period of January 1976 to August 1978. Causes of losses were associated mainly with respiratory involvement (30.8% for adult ewes and 35.9% for unweaned lambs). Type of birth had significantly (p